Characteristics and influencing factors of chemical fertilizer and pesticide applications by farmers in hilly and mountainous areas of Southwest, China. (October 2022) - Tan, Shaojun; Xie, Deti; Ni, Jiupai; Chen, Fangxin; Ni, Chengsheng; Shao, Jingan; Zhu, Dun; Wang, Sheng; Lei, Ping; Zhao, Guangyao; Zhang, Shichao; Deng, Hua
Graphical abstract: Highlights: More fertilizer and pesticides were used in orchard and vegetables. Large-scale farmers used more fertilizers and pesticides than general farmers. Average age, education level and environmental awareness were the main factors. Policy and alternative technology will help to reduce fertilizers and pesticides. Abstract: Studying the characteristics and driving factors of chemical fertilizer and pesticide application of farmers is helpful for the prevention and control of regional non-point source pollution (NPSP). In this study, 320 farmers in Chongqing were surveyed, and the characteristics and main factors influencing chemical fertilizer and pesticide applications were analyzed by spatial analysis and partial least squares regression (PLSR). The results can be showed that: (1) Aaverage unit area applications of N, P2 O5 and pesticide were 6.01 kg/ha/yr, 3.78 kg/ha/yr and 107.89 g/ha/yr. Among them, the fertilizer and pesticide application rates of large-scale households are 8.46 kg/ha/yr/, 5.82 kg/ha/yr and 287.61 g/ha/yr, and the application rates of general farmers are 4.54 kg/ha/yr, 2.55 kg/ha/yr and 40.21 g/ha/yr. Larger amount were applied to orchard and vegetable by large-scale farmer, while larger amounts were applied to grain by general farmers. (2) Fertilizer were spatially agglomerated on a household scale, while pesticide were spatially discrete on a county scale. (3) Average age (AA) of farmers and planting scale (PL) are the main factors affecting fertilizer amounts. Education level (EL), policy guidance (PG), and awareness of environmental effects (AEE) are the main factors influencing pesticide applications. Governments need to formulate rural labor policies and promote land transfer, while also strengthening fertilizer and pesticide reduction policies to enhance farmers' environmental awareness.